A review of the genus Immanus Hulcr & Cognato with a key to species (Coleoptera: Curculionidae: Scolytinae: Xyleborini) - Beaver, R. A.; Sittichaya, W.; Liu, L.-Y. (Zootaxa, 2019)
The four species currently placed in the genus Immanus Hulcr and Cognato are reviewed. Immanus papuanus Beaver, Sittichaya & Liu sp. n. is described. The following new synonymy is proposed: Immanus desectus (Eggers, 1923) (= Xyleborus insignis Browne, 1984 syn. n.). The following new combinations are proposed: Immanus pseudocolossus (Schedl, 1942) comb. n., I. sarawakensis (Eggers, 1923) comb. n., I. trolaki (Schedl, 1939) comb. n., all originally described in Xyleborus. A key to the females of the eight species now included in the genus is provided. The taxonomy, diagnostic characters, distribution and biology of the species are briefly discussed.